2016
DOI: 10.1186/s13071-016-1788-7
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural chemicals: life changer for mosquito vectors in agricultural landscapes?

Abstract: BackgroundAlthough many mosquito species develop within agricultural landscapes where they are potentially exposed to agricultural chemicals (fertilizers and pesticides), the effects of these chemicals on mosquito biology remain poorly understood. This study investigated the effects of sublethal concentrations of four agricultural chemicals on the life history traits of Anopheles arabiensis and Culex quinquefasciatus mosquitoes.MethodsField and laboratory experiments were conducted to examine how sublethal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 66 publications
1
29
0
1
Order By: Relevance
“…A study that attempted to examine the effects of agrochemicals on An. arabiensis reported that nitrate concentration in water bodies has been reported to be over 100 mg L −1 and phosphate over 9.45 mg L −1 . The concentrations used in this study were much lower, yet demonstrate biological effects on mosquitoes.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…A study that attempted to examine the effects of agrochemicals on An. arabiensis reported that nitrate concentration in water bodies has been reported to be over 100 mg L −1 and phosphate over 9.45 mg L −1 . The concentrations used in this study were much lower, yet demonstrate biological effects on mosquitoes.…”
Section: Discussionmentioning
confidence: 61%
“…arabiensis . The runoff of fertilizers and other agrochemicals, particularly those of an inorganic nature, is known to pollute water bodies surrounding crops, creating attractive and nutrient‐rich pools for mosquitoes to breed in . This can lead to increased vector abundance, as has consistently been observed in Kenya for An.…”
Section: Introductionmentioning
confidence: 99%
“…However, these chemicals also cause adverse biological effects on non‐target organisms such as humans, who may be exposed occupationally, as in the case of farmers and pesticide industry workers, and non‐occupationally, through contact with pesticide residues in food, air, and drinking water . Currently, it is estimated that each year 2.4 million tons of pesticides and 180.1 million tons of fertilizers are used worldwide to improve agricultural production …”
Section: Introductionmentioning
confidence: 99%
“…1 Currently, it is estimated that each year 2.4 million tons of pesticides and 180.1 million tons of fertilizers are used worldwide to improve agricultural production. 2 Global data show that pesticides may be responsible for 350 000-440 000 deaths each year, with 99% of poisonings occurring in developing countries. 3 Systematic reviews of the literature have shown that human exposure to pesticides may be associated with chronic, non-cancer effects, including dermatologic, neurologic, reproductive, and genotoxic effects 4 ; and carcinogenic effects, such as lung, breast, pancreatic, brain, prostate, stomach, ovarian, and kidney cancers, as well as non-Hodgkin lymphoma, and leukemia.…”
mentioning
confidence: 99%
“…Though patch size surely plays a role in detection, and larger patches have a greater probability of encounter, patch quality is the primary factor in habitat selection (Fretwell & Lucas, 1970;Wiens, 1976). Resource density (Binckley & Resetarits, 2008;Blaustein & Kotler, 1993), disease (Robertson & Hamilton, 2012), predator presence/absence (Resetarits & Wilbur, 1989;Vonesh & Blaustein, 2010;Vonesh, Kraus, Rosenberg, & Chase, 2009), canopy cover (Binckley & Resetarits, 2007, 2009), productivity (Binckley & Resetarits, 2007) and pesticides (Bentley & Day, 1989;Kibuthu et al, 2016;Takahashi, 2007;Vonesh & Buck, 2007) may all influence perceived patch quality. However, patch quality and patch size are seldom independent, and changes in patch size often affect patch quality, confounding the two, especially when limiting resources are correlated with habitat area (see reviews in Haynes & Cronin, 2004;Krauss, Steffan-Dewenter, M€ uller, & Tscharntke, 2005;Rabasa, Guti errez, & Escudero, 2008).…”
Section: Introductionmentioning
confidence: 99%